Customer concentration and corporate risk-taking - Cao, Yue; Dong, Yizhe; Ma, Diandian; Sun, Li (Journal of Financial Stability, 2021)
This study empirically investigates the relationship between customer concentration and corporate risk-taking. We find that overall customer concentration significantly reduces corporate risk-taking. However, the relationship varies across different settings. Specifically, the negative relationship between customer-base concentration and corporate risk-taking is only significantly present in more marketized regions, more competitive industries, firms with lower market shares, less innovative and non-state-owned firms, and those without major governmental or state-owned-enterprise customers. Moreover, our panel threshold models indicate significant threshold effects. When customer-base concentration is below the first threshold (low concentration level), it is positively associated with corporate risk-taking. When customer-base concentration increases to above the second threshold, the association turns significantly negative, suggesting that a highly concentrated customer base prompts suppliers to take more precautionary measures and avoid excessive risk-taking. Overall, our findings suggest that the concentration of a supplier’s customer base significantly impacts its risk-taking behaviours.